Fun Science Teaching Materials on the Energy Transformation to Promote Students’ Scientific Literacy - Pursitasari, Indarini Dwi; Suhardi, Eka; Putikah, Tuti (Jurnal Penelitian dan Pembelajaran IPA, 2019)
This study aims to develop fun science teaching material on the energy transformation to promote scientific literacy of junior high school students. The research is a four-D design of Research and Development. The validity of designed teaching materials had been determined by experts and science teachers. Scientific literacy achievements and student’s responds were obtained using scientific literacy test and questionnaire on 95 students. Data analysis was carried out in a quantitative descriptive. The result of this study shows the fun science design contains the concepts of energy transformation that are presented contextually in form of comics strip and science songs, the validity score from experts and teachers were 87.5% and 93.5% respectively, N-gain of 62%, and most of students agree with the use of fun science teaching materials. Thus, fun science teaching material can be used in science learning to promote scientific literacy.